Determinants of the hand functions in patients with rheumatoid arthritis (Annals of Medical Research, 2021)
Aim: The aim of this study was to investigate the hand function determinants and related factors of the patients with rheumatoid arthritis (RA).Material and Methods: Thirty nine patients with long standing rheumatoid arthritis were included in the study. Demographic, clinical and laboratory findings of the patients were recorded. Duruoz Hand Index Data (DHI) was used for the assessment of the hand functions. Disease acitivity was calculated by using Disease Activity Score (DAS) 28. In order to evaluate general disability, Health Assessment Questionnaire Disability Index (HAQ-DI) was used. Grip and pinch strengths of the patients were measured by the Jamar dynamometer.Results: Among all the patients, 82.1% were women. Mean age of the patients were 58.03±13.11 years. Mean disease duration was 9.69 ± 8.96 years. Mean grip strength was 16.58±6.74 kg and pinch strength was 4.80±1.75 kg. Statistically significant positive correlation was found between hand functions measured by DHI and morning stiffness, HAQ-DI, Visual Analog Scale (VAS) hand, VAS global, DAS 28 and pinch (p0.01).Conclusion: In this study, the determinants of functional status of the hand were found as disability, being anti-citrullinated protein antibodies (ACPA) positive, disease activity and pinch in patients with RA.Keywords: Rheumatoid arthritis; hand strength; pinch strength.
Keywords: Rheumatoid arthritis; hand strength; pinch strength.